Atomic force microscopy with nanoelectrode tips for high resolution electrochemical, nanoadhesion and nanoelectrical imaging. (31st January 2017) - Nellist, Michael R; Chen, Yikai; Mark, Andreas; Gödrich, Sebastian; Stelling, Christian; Jiang, Jingjing; Poddar, Rakesh; Li, Chunzeng; Kumar, Ravi; Papastavrou, Georg; Retsch, Markus; Brunschwig, Bruce S; et al.
Abstract: Multimodal nano-imaging in electrochemical environments is important across many areas of science and technology. Here, scanning electrochemical microscopy (SECM) using an atomic force microscope (AFM) platform with a nanoelectrode probe is reported. In combination with PeakForce tapping AFM mode, the simultaneous characterization of surface topography, quantitative nanomechanics, nanoelectronic properties, and electrochemical activity is demonstrated. The nanoelectrode probe is coated with dielectric materials and has an exposed conical Pt tip apex of ∼200 nm in height and of ∼25 nm in end-tip radius. These characteristic dimensions permit sub-100 nm spatial resolution for electrochemical imaging. With this nanoelectrode probe we have extended AFM-based nanoelectrical measurements to liquid environments. Experimental data and numerical simulations are used to understand the response of the nanoelectrode probe. With PeakForce SECM, we successfully characterized a surface defect on a highly-oriented pyrolytic graphite electrode showing correlated topographical, electrochemical and nanomechanical information at the highest AFM-SECM resolution. The SECM nanoelectrode also enabled the measurement of heterogeneous electrical conductivity of electrode surfaces in liquid. These studies extend the basic understanding of heterogeneity on graphite/graphene surfaces for electrochemical applications.